Efficacy of various IDM modules against pea diseases in Lahaul valley - KUMAR, PARDEEP (Indian Phytopathology, 2013)
Six modules of disease management were tested in hill ecosystem of North western Himalayas for the management of pea root rot/wilt complex, white rot and powdery mildew diseases in garden pea. The module M IV (seed treatment with carbendazim @ 2.5g/kg of seed followed by spray of triadimefon @ 0.4g/L followed by spray of carbendazim @ 1.0g/L at 50% flowering after 15 days of first spray followed by spray of triadimefon @ 0.4g/L after 15 days of second spray) gave the highest disease control on pooled mean basis i.e. 77.3, 51.7 and 74.4% followed by M III comprising of seed treatment with carbendazim @ 2.5g/kg of seed followed by spray @ 1.0g/L at 50% flowering followed by two sprays of Hexaconazole (Sitara 5EC) @ 0.5ml/L at15 days resulted 67.5%, 35.9% and 71.9% disease control of root rot, white rot and powdery mildew, respectively. All the modules led to significant green pod yield enhancement with the highest 33.3% in M IV, 22.0% in M I and 21.7% in M III modules over the check. In terms of percent disease index (PDI), pod yield and yield contributing characters viz. plant height, pods/plant, length of pod, breadth of pod and seeds/pod, module M IV and M III performed better than other modules.